Knowledge, attitude and preventive practices related to novel Coronavirus Infection (COVID-19) among patients attending dental hospital in Dharwad - Shekarappa, Hema Tyavanige; Guttal, Kruthika Satyabodh; Iyer, Varuni; Gupta, Vani; Shetty, Preeta (Asian Journal of Medical Sciences, 2020)
Background: The Novel Coronavirus Disease 19 (COVID-19) is one of the deadly diseases declared as pandemic by WHO. The managing strategies include prevention of spread of the infection and awareness regarding the preventive practices, which are very vital in preventing the exponential spread of the disease. Despite the rolling commentary over telephone calls and advertisements at every desk, public is too negligent over this global threat. Aims and Objectives: The present questionnaire based study was aimed to assess the knowledge, attitude and preventive practices existing among the public to face the pandemic. Materials and Methods: The present study was a cross-sectional questionnaire based study using a convenience sampling method. The patients attending the outpatient section of the Oral Medicine department of a Dental Hospital for various dental complaints were interviewed by telephonic conversation. Patient’s knowledge and awareness regarding the prevailing situation created by the media was assessed. Results: Seventy-seven point seven percent of the participants were following the preventive practices. They had an average attitude towards the prevention of spread of infection (52.4%) and considering COVID-19 as a serious infection (51.8%). Younger population, professionals and females had an overall better Knowledge, Attitude and Practices. Conclusions: Majority of the assessed population had a sound knowledge about the pandemic. Certain key issues like visiting the hospitals only for emergencies needs to be emphasised by health care professionals to prevent the spread of the disease.